Benign intermittent upbeat nystagmus in infancy: A new clinical entity. (March 2015) - Robert, Matthieu P.; Michel, Sarah; Adjadj, Elias; Boddaert, Nathalie; Desguerre, Isabelle; Vidal, Pierre-Paul
Abstract Background Upbeat nystagmus in childhood is a rare phenomenon, which is classically associated with neurological or anterior visual pathway dysfunction. Methods We report a series of five infants with an intermittent upbeat nystagmus, without any other ocular or neurological abnormality, having spontaneously resolved before the age of 14 months. Results Nystagmus beating frequency was between 1.5 and 2.5 Hz for all patients, amplitude was remarkably large due to a baseline position in downgaze. The nystagmus mostly occurred in supine position and could be triggered by head rotations in the supine position. Age of onset was from the first weeks of life to two months; age of resolution was 5–14 months. All infants underwent complete clinical examination with ophthalmological, oto-neurological and neurological assessments and MRI-scan. Conclusions Clinical characteristics of the nystagmus suggest an involvement of the otolithic system, with a secondary recalibration of the vestibulo-ocular pathways; however, no obvious vestibular abnormality was found. The pathophysiology of this nystagmus therefore remains unclear.